2006
DOI: 10.1385/bter:110:2:119
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Serum Titanium: Assessment as an Indicator of Exposure to Ammonium Citratoperoxotitanate (IV) and Its Influence on Renal Function

Abstract: Ammonium citratoperoxotitanate IV (TAS-FINE) is a water-soluble titanium complex used to synthesize a photocatalytic titanium(IV) oxide film. This study was aimed to investigate the LD50, dose-response, time-course response, and renal toxicity of TAS-FINE using an animal model. Serum titanium (S-Ti) and its 24-h urinary excretion (U-Ti) were determined by inductively coupled plasma-argon emission spectrometry (ICPAES) after a single oral TAS-FINE administration to male Wistar rats. The LD50 of TAS-FINE was 7.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As described in a previous study by our group [17] and in other publications [1,2,[18][19][20], ICP-AES has been widely used for the determination of trace element concentrations, including REEs in a variety of samples [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…As described in a previous study by our group [17] and in other publications [1,2,[18][19][20], ICP-AES has been widely used for the determination of trace element concentrations, including REEs in a variety of samples [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that titanium and vanadium are excreted mainly through urine, and urinary concentrations of titanium and vanadium are good indicators for the exposure of the corresponding compounds (14,15). The present study evaluated the associations of urinary levels of titanium and vanadium with breast cancer risk in an ongoing case-control study carried out in Guangzhou, China.…”
Section: Introductionmentioning
confidence: 98%